Evaluating Existing Literature on Interreligious Dialogue and Peacebuilding in Sri Lanka: Buddhist-Muslim Relationships - Arkam, Mohamed; Shehu, Fatmir (IIUM Journal of Religion and Civilisational Studies, 2024)
This study evaluates selected literature on interreligious dialogue and peacebuilding in Sri Lanka emphasising Buddhist-Muslim relationships. A comprehensive review of critical findings of existing scholarship about the current state of interreligious dialogue, its role in peacebuilding, and the challenges it faces in the Sri Lankan context is provided. This evaluation aims to identify the need for more empirical research on interreligious dialogue’s efficacy in lowering religious tensions and creating societal peace in Sri Lanka. While such dialogue has the potential to foster unity and peace, it faces significant obstacles such as religious fanatism, negative stereotypes, and misunderstanding. The lack of empirical studies and theoretical frameworks implies that future studies are needed to properly understand interreligious dialogue in Sri Lanka and its role in peacebuilding. This study uses historical, descriptive, and analytical methods. This study uses two significant strategies to pick appropriate materials for this evaluation: first, widely accepted experts’ most celebrated chapter works, and second, some important selected papers published in reputed journals. The focus of discussion is on (1) Historical interactions between Buddhists and Muslims and lessons for dialogue; (2) Post-war dynamics and the need for dialogue; (3) The role of interreligious dialogue in peacebuilding; (4) Challenges to interreligious dialogue in Sri Lanka; and (5) Analytical Remarks. The study concludes that interreligious dialogue has great potential to enhance peacebuilding efforts in Sri Lanka’s multi-religious community, especially in strengthening Buddhist-Muslim relationships.